INVADED HOUSE, (RE)INVENTED ART (Olhares, 2020)
This article uses the short story “Casa Tomada”, by the Argentine writer Júlio Cortázar, as a scope of discussion. In addition, it relates concepts by Gardón Bachelard and Constantin Stanislavski to speak of “home” and its art-political elements. It exemplifies the topics covered, based on artistic productions published on social networks during the Covid-19 pandemic, especially on Instagram. It deals with the right to housing as a social responsibility.